Sistem Pendukung Keputusan Pemilihan Siswa Penerimaan Bantuan Program Indonesia Pintar Menerapkan Kombinasi Metode Rank Order Centroid Dan Additive Ration Assassment - Purba, Maya Pratiwi (Journal of Decision Support System Research, 2024)
Program Indonesia Pintar (PIP) is an educational cash assistance from the government that finances students until they graduate from high school from the age of 6-12 years. the target of receiving the Indonesia Pintar Program (PIP) is the acceptance of the family hope program (PKH) or the acceptance of the prosperous family card (KKS) who come from underprivileged families. The provision of this assistance is often not on target, this is because the calculation of PIP acceptance still uses a manual system and has not been computerised. The ARAS method is expected to assist in the selection of students who are eligible to receive PIP assistance, because the ARAS method will carry out the ranking process based on criteria with different weights so that the results are more optimal. This research is to find the weight value for each criterion, then carry out a ranking process that will determine the optimal alternative as well in the selection of students receiving smart Indonesia card assistance. as for the 5 criteria that are used as a reference in the selection of students receiving smart Indonesia card assistance are having a prosperous family card (KKS), Participants in the Family Hope Card Program (PKH), Orphans, Disabilities and Victims of Natural Disasters or Calamities.